2021
DOI: 10.33714/masteb.917788
|View full text |Cite
|
Sign up to set email alerts
|

Ice-Ice Disease in Commercially Cultivated Seaweeds Kappaphycus spp. and Eucheuma spp.: A Review on the Causes, Occurrence, and Control Measures

Abstract: Kappaphycus spp. and Eucheuma spp. are two economically significant seaweed species cultivated globally due to their carrageenan content with numerous commercial applications. They are mainly cultivated in the Philippines, Indonesia, Malaysia, and Tanzania. The culture of these seaweeds also provides income sources for many coastal dwellers. In 2018, the total global production from these seaweeds was about 11 million tonnes. One of the primary problems that affect seaweed production is the incidence of iceice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Also, AMPEP significantly increased the growth rate (7.3%) in K. alvarezii (Loureiro et al, 2014), relatively higher than our study. The ice-ice disease of Kappaphycus is usually associated with changes in environmental factors like light intensity, salinity, and temperature manifested with extensive whitening of the branches, which are further degraded by the presence of opportunistic bacteria (Largo et al, 1995a and1995b;Tahiluddin andTerzi, 2021a andTahiluddin et al, 2021c). Likewise, marine-derived fungi were reported to be a potential causative agent of this disease (Solis et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, AMPEP significantly increased the growth rate (7.3%) in K. alvarezii (Loureiro et al, 2014), relatively higher than our study. The ice-ice disease of Kappaphycus is usually associated with changes in environmental factors like light intensity, salinity, and temperature manifested with extensive whitening of the branches, which are further degraded by the presence of opportunistic bacteria (Largo et al, 1995a and1995b;Tahiluddin andTerzi, 2021a andTahiluddin et al, 2021c). Likewise, marine-derived fungi were reported to be a potential causative agent of this disease (Solis et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The genus of Kappaphycus is an economically important red seaweed cultured in both tropical and subtropical waters. This red seaweed is highly marketable worldwide owing to its carrageenan content, which is extensively utilized in food and non-food products as a binder, emulsifier, gelling, and YYU J AGR SCI 32 (2): 436-447 Tahiluddin et al / Use of Some Brown Seaweed Extracts as Bio-fertilizers and their Effects on the Ice-ice Disease Occurrence, Carrageenan Yield, and Growth Rate of the Red Seaweed Kappaphycus striatus thickening agents (Hurtado et al, 2000;Hurtado et al, 2015;Tahiluddin and Terzi, 2021a). The Philippines is a major seaweed producer, ranking fourth globally (FAO, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…can quickly adhere to and dominate seaweed tissue as a first stage in the infection process, based on its motile capabilities ( Largo et al, 1995 , 1998 ). When exposed to harsh conditions, the bacteria can use carrageenan in seaweed thalli as a carbon source by reaching the medullary layer of diseased branches ( Tahiluddin and Terzi, 2021 ). A similar ability of Pseudoalteromonas carrageenovora to produce the specific κ -carrageenase enzyme and degrade κ -carrageenan in K. alvarezii suggested that this bacterium might cause “ice–ice” disease symptoms such as thalli whitening and scaling ( Riyaz et al, 2019 ).…”
Section: Factors Affecting Carrageenan Yield and Productionmentioning
confidence: 99%